Metamizole does not affect fracture healing in a murine ischemia model - Schönbeck, Christian; Stutz, Janine; Schreiber, Sebastian T.; Keller, Lukas; Siep, Chiara; Metzger, Wolfgang; Giorgi, Mario; Sartini, Irene; Fritz, Tobias; Pohlemann, Tim; Menger, Michael D.; Liodakis, Emmanouil; et al. (Frontiers in Physiology, 2025)
Metamizole is a commonly used analgesic drug in clinical fracture management, which does not affect the healing process under physiological conditions. However, many fracture patients suffer from co-morbidities resulting in ischemic conditions with impaired bone healing. The effect of metamizole on fracture healing under ischemic conditions has not been analyzed so far. Accordingly, in this study 44 CD-1 mice underwent ligation of the deep femoral artery to induce mild ischemia in the right hind limb. The femur was then fractured and stabilized with an intramedullary lag screw and the animals were daily treated per os with 50 mg/kg metamizole (n = 23) or vehicle (control; n = 21). Serum concentrations of the active metamizole metabolites, 4-methyl-amino-antipyrine (4-MAA) and 4-amino-antipyrine (4-AA), were determined 30, 60 and 90 min after administration. Bone healing was analyzed by biomechanical, radiological, histomorphometrical and Western blot analysis at 2 and 5 weeks postoperatively. The plasma level of 4-MAA was high at all time points, whereas 4-AA peaked at 90 min after administration. Biomechanical, radiological and histomorphometrical analyses revealed no differences between metamizole-treated and control mice, while both groups showed a delayed fracture healing. Of interest, Western blot analyses of callus tissue showed an increased expression of the pro-angiogenic factor Cyr61 and the osteoanabolic runt-related transcription factor 2 (RUNX2) as well as the osteocatabolic receptor activator of NF-κB ligand (RANKL) in metamizole-treated animals when compared to controls. Taken together, these findings indicate that the application of metamizole does not affect fracture healing under ischemic conditions. Therefore, treatment with this analgesic drug may be also recommended in fracture patients suffering from co-morbidities resulting in tissue ischemia.